(untitled) (Research, Society and Development, 2020)
The article is based on the results obtained during the realization of the case study on the socio-environmental analysis of the Buriti stream, in the municipality of Pontes and Lacerda-MT, as a closure of the activities carried out by the Human Sciences Training Center-CEFAPRO. The activities of implementation and completion of the training were carried out by History and Geography teachers, with the cooperation of students from the second year of High School at the 14 de Fevereiro State School. In order to carry out the research, studies were carried out and on-site visits were carried out to recognize the study area and then analyze and compare the data found. This experience proved to be rewarding, since it was possible to understand the dynamics of the valley bottoms and the functioning of the urban streams, as is the case of the Buriti Stream, of undeniable historical and natural importance for the city and its residents. The article aims to encourage more studies on stream ecosystems in urban areas, as well as to mobilize the population to assume environmentally sustainable behaviors.